Penerapan Microsoft Project dalam Metode Crashing Terhadap Waktu dan Biaya - Mahendra, Muhammad Oka; Saputro, Teguh Eko; Putra, Al Fiillian Sah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The PPLP Banten Building construction project experienced significant delays due to the extension of the implementation time, design revisions (shop drawings), and inaccurate material delivery. This study implemented a schedule compression strategy using Microsoft Project with two acceleration alternatives based on the AHSP standard. The crashing research method. The results of the study showed that the project duration was successfully shortened by 678 days with the 4-hour/day overtime alternative, while further work shift optimization reduced the duration to 530 days. Cost analysis showed differences between the two alternatives: with 4-hour/day overtime, the acceleration cost reached IDR3,066,675,000 (AHSP), while the work shift only cost IDR1,223,565,000 (AHSP). Comparison of cost slopes strengthened the advantages of work shifts: 4-hour/day overtime resulted in a cost slope of IDR193,067,245.23/day (AHSP), while the work shift only cost IDR33,638,199.58/day (AHSP). Evaluation of total costs (direct and indirect) also confirmed the efficiency of work shifts, with direct costs of Rp9,512,731,986.58 and indirect costs of Rp1,273,456,116.78, compared to 4 hours/day of overtime which required direct costs of Rp9,672,161,032.20 and indirect costs of Rp1,322,728,805.77.